2017
DOI: 10.1108/md-10-2015-0465
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of brand experiences on brand loyalty: mediators of brand love and trust

Abstract: Purpose-1).Prior studies on brand relationships tend to overlook the mediator(s) between the relationships between brand experience and brand loyalty. Hence, the main purpose of this paper is to examine these mediating roles of brand love and brand trust on the brand experience and brand loyalty relationships. 2).While the literature does not examine the distinct dimensions of brand experience and brand loyalty, this study fills up this gap and examines their detailed dimensions and effects on brand loyalty. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

46
308
2
71

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(427 citation statements)
references
References 78 publications
(144 reference statements)
46
308
2
71
Order By: Relevance
“…Although this relation is not commonly found in the literature, this disparate degree of importance among brand experience dimensions was already found in previous studies. For example, a study of mobile phone brands found sensory experience as the major driver of brand love (Huang, 2017). This finding is also in line with Koo and Kim (2013) that examined the influence of several store environmental cues on store emotional attachment (brand love).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…Although this relation is not commonly found in the literature, this disparate degree of importance among brand experience dimensions was already found in previous studies. For example, a study of mobile phone brands found sensory experience as the major driver of brand love (Huang, 2017). This finding is also in line with Koo and Kim (2013) that examined the influence of several store environmental cues on store emotional attachment (brand love).…”
Section: Resultssupporting
confidence: 69%
“…The results point to the importance of brand love to customer loyalty, both directly and indirectly through customer satisfaction. This finding echoes in the scarce research supporting the path from brand love to customer loyalty (Bergkvist and Bech-larsen, 2010;Huang, 2017). Bergkvist and Bech-larsen (2010) in a study of six brands found that brand love has a positive influence in brand loyalty.…”
Section: Resultsmentioning
confidence: 52%
“…Past research indicates that delivering brand experiences results in positive consumer outcomes, including stronger brand personality associations, consumer satisfaction and brand loyalty (Brakus et al, ), brand equity (Lin, ), word‐of‐mouth (Klein, Falk, Esch, & Gloukhovtsev, ), brand trust and brand love (C. C. Huang, ). Despite the importance of brand experience, studies on its antecedents are, however, quite rare.…”
Section: Research Background and Hypothesesmentioning
confidence: 99%
“…Brand trust refers to the expectation that consumers have about a brand and particularly that the brand will consistently accomplish its promise and deliver value for the benefit of the consumer, and for the least, not perniciously (Doney and Cannon, 1997;Mayer et al, 1995). It is a major dimension of consumers' relationships with brands since it influences brand equity (Delgado-Ballester and Munuera-Alemán, 2005), brand loyalty (Chaudhuri and Holbrook, 2001;Delgado-Ballester and Munuera-Alemán, 2001;Frasquet et al, 2017;Huang, 2017;Menidjel et al, 2017;Sung and Kim, 2010;Veloutsou, 2015), brand commitment (Ha, 2004;Morgan and Hunt, 1994), and purchase intentions (Bhandari and Rodgers, 2018;Sichtmann, 2007).…”
Section: Brand Trustmentioning
confidence: 99%